Pelatihan Pemasaran Menggunakan Media Sosial Instagram Pada Usaha Jasa Jahit Kebaya Meka Tailor - Putu Safitri Pratiwi, Luh; Made Pasek Pradnyana Wijaya, I; Ayu Meitridwiastiti, A.A; Wayan Astu Werdistira, I (COVIT (Community Service of Tambusai), 2023)
Meka Tailor owned by Mrs. Ni Nyoman Mekawati is a kebaya sewing service business located in the Saba Village area, Gianyar, Bali. This thriving business was built around 2020 during the covert pandemic. At the beginning of this business, partners received all forms of sewing orders for clothes. But along with the dominance of kebaya orders, partners are now focusing on kebaya sewing services. In receiving his orders, partners only rely on a network of friends and relatives who already know him. This is because partners have not yet marketed this business through this growing internet medium. The orders that came were also not small. In just one day, partners are able to process at least 3 kebaya sewing orders that must be completed. Sometimes there are no orders coming in for a while, which results in no income for partners. The purpose of this service activity is to introduce Instagram social media to help market the kebaya sewing service business owned by partners. Keywords: training; kebaya; social media; instagram